Exploring biofertilizer potential of plant growth-promoting rhizobacteria candidates from different plant ecosystems - Dwi Agustiyani; Tirta Kumala Dewi; Nur Laili; Achirul Nditasari; Sarjiya Antonius (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Agustiyani D, Dewi TK, Laili N, Nditasari A, Antonius S. 2021. Exploring biofertilizer potential of plant growth-promoting rhizobacteria candidates from different plant ecosystems. Biodiversitas 22: 2691-2698. Plant growth-promoting rhizobacteria (PGPR) have been widely used as inoculants to increase the growth of crops. This study aims to evaluate the effective PGPR strains according to their capability in various plant growth-promoting activities in vitro. Ten rhizosphere soil samples were obtained from several plant ecosystems in Bangkinang, Kampar, Sumatra Island, Indonesia. A total of 42 bacteria were isolated and tested for three plant growth–promoting activities i.e., phosphate solubilization, indole-3-acetic acid (IAA) production, and N fixation. Out of 42 isolates, 26 were positive for phosphate solubilization, 11 were positive for IAA production, and five were positive for N fixation. The qualitative and quantitative analysis of plant growth–promoting activities revealed that the highest phosphate solubilizing isolate was PK.4.2 (SI 4.33); the highest IAA-producing isolate was I.4.2 (73.1 ppm); while the highest N-fixing ability was NFB.1.1. According to the seed bioassay results, the shoot and root length of bok choy (Brassica rapa) seedlings were significantly enhanced with the PGPR isolates treatment. The highest shoot length (2.53 cm) was observed among seeds treated with I.4.2 isolate, followed by PK.6.1 (2.45 cm) and I.5.3 (2.07 cm). The NFB.1.1 isolate promoted the longest root length (6.4 cm), although this was similar with I.5.3 isolate (6.11 cm). Two isolates that showed significant plant growth–promoting activities were analyzed using 16S rDNA sequences. The two isolates had a close evolutionary relationship with genus Sinomonas strain Cw 108 (I.4.2) and Arthrobacter (I.5.3.).